ANALYSIS OF LANGUAGE FUNCTIONS IN THE SHORT STORY THE SUMMER SOLSTICE BY NICK JOAQUIN - Mary Joy C. Cahigus; Kay Tepait Juanillo (English Language Education Department, Faculty of Teacher Training and Education, Syekh-Yusuf Islamic University (PBI FKIP UNIS), 2023)
Language and literature are essentially connected, and one cannot function without the other. Thus, this study analyzes the language functions used by the main characters in the short story The Summer Solstice by Nick Joaquin. This study aims to determine the types of Language functions in the short story and identify the most dominant language function used by the main characters. Moreover, the study also aims to analyze the context of the language functions identified. The researchers used Janet Holmes’ Theory of Language Function (2013) to analyze the utterances of the main characters and Dell Hymes' SPEAKING Model to analyze the context of the language functions in each utterance. The researchers then applied the descriptive qualitative design to systematically analyze the data. The result of this study shows that out of the eight (8) language functions identified by Janet Holmes (2013), only seven (7) types of language functions were found in the short story, namely expressive, directive, heuristic, referential, metalinguistic, phatic functions. On the other hand, poetic function was not found in this research. The findings revealed that this story dominantly uses expressive functions, in which the speaker's emotion is what captures the interest of the readers.